(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
تم تحضير عينات سيراميكية من تيتانات الباريوم المشوبة بالكالسيوم انطلاقا من مواد أولية عالية النقاوة بطريقة تفاعل الحالة الصلبة، ولبدت العينات السيراميكية عند الدرجة 1350˚C لمدة 3h. دُرست الخصائص الكهربائية للعينات السيراميكية Ba1-xCaxTiO3 من أجل النسب (x= 0, 0.1, 0.3, 0.5, 0.7, 1)، كتابع لدرجات الحرارة ضمن المجال من 25˚C إلى 220˚C عند التردد 1kHz. أظهرت النتائج التجريبية انتقال نقطة كوري ضمن مجال درجات الحرارة من 120˚C إلى 150˚C بتغير نسب الكالسيوم. يتناقص ثابت العزل الكهربائي بزيادة نسب الكالسيوم المضافة. بلغت أكبر قيمة لثابت العزل الكهربائي 6898.85=έ لتيتانات الباريوم عند نقطة كوري Tc=132˚C. تم الحصول على قيم مرتفعة لظل زاوية الفقد عند طرفي مجال درجات الحرارة المدروس. يتناقص ثابت كوري للعينات المدروسة بزيادة نسب الكالسيوم المضافة. Ceramic samples of calcium doped barium titanate have been prepared from high-purity raw materials by using solid-state reaction method at a sintering temperature of 1350˚C for 3.5h. The electrical properties of ceramic samples Ba1-xCaxTiO3 have been studied for the ratios (x = 0, 0.1, 0.3, 0.5, 0.7, 1), as a function of temperature within the range of 25˚C to 220˚C at the frequency 1kHz. Experimental results show that the Currie point moved within the temperature range from 120˚C to 150˚C by change of calcium-added ratios. Dielectric constant decreases by increasing the calcium-added ratios. The maximum value of the dielectric constant rached to έ=6898.85 for barium titanate at the temperature Tc = 132˚C. We got the high values of the tangent loss angle at both ends of the studied temperature range. Curie constant decrease of the samples by increasing the additional calcium ratios.